The inhibitor of differentiation-1 (Id1) enables lung cancer liver colonization through activation of an EMT program in tumor cells and establishment of the pre-metastatic niche. (28th August 2017) - Castañón, Eduardo; Soltermann, Alex; López, Inés; Román, Marta; Ecay, Margarita; Collantes, María; Redrado, Miriam; Baraibar, Iosune; López-Picazo, José María; Rolfo, Christian; Vidal-Vanaclocha, Fernando; Raez, Luis; et al.
Abstract: Id1 promotes carcinogenesis and metastasis, and predicts prognosis of non-small cell lung cancer (NSCLC)-adenocarcionoma patients. We hypothesized that Id1 may play a critical role in lung cancer colonization of the liver by affecting both tumor cells and the microenvironment. Depleted levels of Id1 in LLC (Lewis lung carcinoma cells, LLC shId1) significantly reduced cell proliferation and migration in vitro . Genetic loss of Id1 in the host tissue ( Id1 −/− mice) impaired liver colonization and increased survival of Id1 −/− animals. Histologically, the presence of Id1 in tumor cells of liver metastasis was responsible for liver colonization. Microarray analysis comparing liver tumor nodules from Id1 +/+ mice and Id1 −/− mice injected with LLC control cells revealed that Id1 loss reduces the levels of EMT-related proteins, such as vimentin. In tissue microarrays containing 532 NSCLC patients' samples, we found that Id1 significantly correlated with vimentin and other EMT-related proteins. Id1 loss decreased the levels of vimentin, integrinβ1, TGFβ1 and snail, both in vitro and in vivo . Therefore, Id1 enables both LLC and the host microenvironment for an effective liver colonization, and may represent a novel therapeutic target to avoid NSCLC liver metastasis. Highlights: Liver involvement in NSCLC ranges from 20 to 40% during the disease course and conferring a poorer prognosis at any stage. Id1 enables the tumor and the microenvironment to colonize the liver but the host tissue results more relevant for metastasis. Id1 confers an EMT program and induces expression of the prometastatic protein vimentin in the liver and tumor cells. Id1 may represent a novel therapeutic target to avoid NSCLC liver metastasis.